Chondroprotection by urocortin involves blockade of the mechanosensitive ion channel Piezo1 - K. M. Lawrence (Nature Portfolio, 2017)
Abstract Osteoarthritis (OA) is characterised by progressive destruction of articular cartilage and chondrocyte cell death. Here, we show the expression of the endogenous peptide urocortin1 (Ucn1) and two receptor subtypes, CRF-R1 and CRF-R2, in primary human articular chondrocytes (AC) and demonstrate its role as an autocrine/paracrine pro-survival factor. This effect could only be removed using the CRF-R1 selective antagonist CP-154526, suggesting Ucn1 acts through CRF-R1 when promoting chondrocyte survival. This cell death was characterised by an increase in p53 expression, and cleavage of caspase 9 and 3. Antagonism of CRF-R1 with CP-154526 caused an accumulation of intracellular calcium (Ca2+) over time and cell death. These effects could be prevented with the non-selective cation channel blocker Gadolinium (Gd3+). Therefore, opening of a non-selective cation channel causes cell death and Ucn1 maintains this channel in a closed conformation. This channel was identified to be the mechanosensitive channel Piezo1. We go on to determine that this channel inhibition by Ucn1 is mediated initially by an increase in cyclic adenosine monophosphate (cAMP) and a subsequent inactivation of phospholipase A2 (PLA2), whose metabolites are known to modulate ion channels. Knowledge of these novel pathways may present opportunities for interventions that could abrogate the progression of OA.